Class 1 integrons and multiple mobile genetic elements in clinical isolates of the Klebsiella pneumoniae complex from a tertiary hospital in eastern China - Wang, Lan; Zhu, Mei; Yan, Chunxia; Zhang, Yanfang; He, Xuying; Wu, Lin; Xu, Jiefeng; Lu, Junwan; Bao, Qiyu; Hu, Yunliang; Xu, Teng; Liang, Jialei (Frontiers in Microbiology, 2023)
Background The emergence of highly drug-resistant K. pneumoniae, has become a major public health challenge. In this work, we aim to investigate the diversity of species and sequence types (STs) of clinical Klebsiella isolates and to characterize the prevalence and structure of class 1 integrons. Methods Based on the whole genome sequencing, species identification was performed by 16S rRNA gene homology and average nucleotide identity (ANI) analysis. STs were determined in accordance with the international MLST schemes for K. pneumoniae and K. variicola. Integron characterization and comparative genomic analysis were performed using various bioinformatic tools. Results Species identification showed that the 167 isolates belonged to four species: K. pneumoniae, K. variicola subsp. variicola, K. quasipneumoniae and K. aerogenes. Thirty-six known and 5 novel STs were identified in K. pneumoniae, and 10 novel STs were identified in K. variicola subsp. variicola. Class 1 integrons were found in 57.49% (96/167) of the isolates, and a total of 169 resistance gene cassettes encoding 19 types of resistance genes, including carbapenem resistance gene (blaIPM-4) and class D β-lactamases gene (blaOXA-1 and blaOXA-10), were identified. Among the 17 complete genomes, 29 class 1 integrons from 12 groups were found, only 1 group was encoded on chromosomes. Interestingly, one plasmid (pKP167-261) carrying two copies of approximately 19-kb IS26-Int1 complex resistance region that contains an integron and a multidrug resistance gene fragment. Conclusion The results of this work demonstrated that the species and STs of the clinical Klebsiella isolates were more complex by the whole genome sequence analysis than by the traditional laboratory methods. Finding of the new structure of MGEs related to the resistance genes indicates the great importance of deeply exploring the molecular mechanisms of bacterial multidrug resistance.